Diagnóstico de la contaminación por mercurio, plomo, arsénico, antimonio y cadmio en el sedimento de la cuenca del Río Siete, en los sectores correspondientes a la quebrada La Florida y la quebrada El Paraiso en el área del cantón Ponce Enríquez, provincia del Azuay, para prevenir daños a su sistema ecológico. - Cedillo Cherres, Henry G (2008)
Whit the purpose of finding out the level of contamination in the basic of the River Seven been carried out a series of analysis of five heavy metals mercury, lead, arsenic, antimony and cadmium, during the months of August, September, October of the years 2007, taking samples of grain silt dies every month, the same ones that took in the gulches The Florida and The Paradise adjacent to mining industries.